Políticas públicas de inovaç\~ao no setor agropecuário: Uma avaliaç\~ao dos fundos setoriais - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The aim of this paper is to analyze the sectoral funds directed to agribusiness (CTAgribusiness). Besides presenting the national system of agricultural innovation in Brazil, the study shows the dynamic of technological development related to agribusiness sectoral funds. A description of the projects related to agriculture is presented, even if they received support from other instruments, particularly from other sectoral funds. Results show that the CT-Agribusiness converts basic science into technological innovation. Finally, different policies to promote technological innovation are discussed.
Keywords: Q16; O3; O2; O38; 330; agricultural technology; technological change; innovation public policies; Agroindustrie; Agrartechnik; Technischer Fortschritt; Innovationspolitik; Brasilien